Lava flow daily monitoring: the case of the 19 September–5 October 2022 eruption at Piton de la Fournaise - Chevrel, Magdalena Oryaëlle; Villeneuve, Nicolas; Grandin, Raphaël; Froger, Jean-Luc; Coppola, Diego; Massimetti, Francesco; Campus, Adele; Hrysiewicz, Alexis; Peltier, Aline (Volcanica, 2023)
Taking prompt and effective actions to mitigate risks associated with an effusive eruption greatly depends on the monitoring of lava flow emplacement. Here we report on the monitoring of the lava flow emplaced during the 19 September to 05 October 2022 eruption at Piton de la Fournaise (La Réunion) that involves an unprecedentedly large data set acquired using multiple techniques and sensors. These include aerial photogrammetry to construct digital surface models and define lava flow geometry during and after emplacement. Complementary use of multiple satellite sensors (visible, infrared, and radar) allowed lava flow field contour definition and an estimation of time-averaged discharge rate with daily frequency. Evolution of the eruptive cone morphology was also monitored through aerial photogrammetry and radar multi-viewing angle imagery. This combination of data obtained from several institutes and using various techniques—from ground, air and space—allowed detailed tracking of lava flow advance and serves as an example for future eruptions at Piton de La Fournaise and at other active volcanic sites.